Greener Fischer-Tropsch processes for fuels and feedstocks - Maitlis, Peter M.; Klerk, Arno de. (Weinheim, Germany : Wiley-VCH, 2013)
A comprehensive and up-to-date overview of this process, from the basic science to commercial issues. In addition to the chemical and industrial side of Fischer-Tropsch synthesis, this monograph deals with process economics as well as such ""green"" concepts as sustainability and environmental care. The result is a practical reference for researchers and engineers working on fuel processing or fuel cell technologies in industry, while equally serving as a great introductory book for graduate courses in chemistry and chemical engineering.
pt. 1. Introduction -- pt. 2. Industrial and economics aspects -- pt. 3. Fundamental aspects -- pt. 4. Environmental aspects -- pt. 5. Future prospects.
Includes bibliographical references and index.
Keywords: Fischer-Tropsch process; Liquid fuels; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Fischer-Tropsch process; Liquid fuels; Electronic books